Bioactive composition and anti-hyperglycemic properties of biofortified yellow maize-based gluten-free cookies - Abdulrazaaq, Khadijat Oluwashola; Imam, Yunus Temitayo; Irondi, Emmanuel Anyachukwu; Ajani, Emmanuel Oladipo (Frontiers in Food Science and Technology, 2024)
The gluten-free cookies (GFC) made from biofortified yellow maize were assessed for their bioactive components (flavonoids, tannins, and saponins), carotenoids, starch-hydrolyzing enzymes (alpha-amylase and alpha-glucosidase), and glycemic index. After adding sodium carboxyl methylcellulose (SCMC), a reference hydrocolloid, and Brachystegia eurycoma flour (BEF) to the biofortified yellow maize flour (BYF) in four different ratios (2.5, 5, 7.5, and 10%), respectively, the blends were used to produce the GFC. Cookies made with commercial wheat flour (100% CWF) were used as the control. The total flavonoid contents of the 100% BYF cookies (144.48 ± 0.18 mg/g) and saponins (1.04 ± 0.00 mg/g) were significantly (p < 0.05) higher than the 100% CWF cookies (93.84 ± 0.36 mg/g; 1.02 ± 0.00 mg/g). The total tannin contents of the cookies ranged from 3.12 ± 0.00 mg/g (100% CWF) to 4.87 ± 0.00 mg/g (2.5%BEF-97.5% BYF). The carotenoid profiles indicated the presence of lutein (range from 0.62 to 1.63 µg/g), β-carotene (range from 3.81 to 6.06 µg/g), β-cryptoxanthin (range from 0.19 to 1.75 µg/g) and zeaxanthin (range from 0.83 to 2.48 µg/g) in the cookies. Further, the GF cookies significantly (p < 0.05) inhibited the alpha-amylase (IC50 value ranged from 1.42 ± 0.01 µg/mL (100% BYF) to 2.63 ± 0.01 µg/mL (100% CWF)) and alpha-glucosidase with IC50 value range from 1.12 ± 0.01 µg/mL (2.5%SCMC-97.5% BYF) to 6.72 ± 0.01 (7.5%BEF-92.5% BYF). The GF cookies showed a low glycemic index (GI) value (GI < 50). The biofortified yellow maize-based GF cookies have significant amounts of bioactive 2 compounds, anti-hyperglycemic properties, and low GI. Hence, they can serve as functional baked food with potential health benefits.